Palavras que dançam à beira de um abismo: mulher na dramaturgia de Hilda Hilst - Fuser, Marina Costin (2012)
This present dissertation throws light upon a theater written through the shadows of Brazilian dictatorship. Hilda Hilst s dramaturgy is a scream of protest facing the arbitrariness portrayed by the executioners of the regime. Among the ruins of human barbarism, the lady warrior shines. Though the analysis of two of Hilda Hilst s plays The Enterprise / The Possessed story of austerity and exception (1969) I intend to map the trails of women that serached the path of transcendence. Her lyrism is related to possissibilities, mouvements, and game turns. The woman in Hilda Hilst does not suit closed definitions; it unfolds just like a hand fan, made by multiple layers. Hilst enhances the trasitory, in the heat of metamorphic processes that come across her characters. Her dramaturgy is composed by allegories, that interweave in a delicate fabric, where poetry and theatre combine. The purpouse of this work is to go through these labyrinthic paths, in a senstive analysis of the unfoldings of this lyrism which does not let itself be fixed. Which silences and which screams inhabit her characters, and what happens when they are driven to their extreme limits?